Participation of Statistical Committees and Scientific Public Organizations of Siberia in Population Censuses in the Second Half of the 19th Century - E. V. Igumnov (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The interrelation between development of the state, administrative statistics, scientific knowledge and organization of population censuses in the European countries and Russia is considered. Formation is traced and the main directions of activity of provincial and regional statistical committees are revealed. Particular attention is paid to the role of Siberian statistical committees in organizing the city one-day and the first general population census of the Russian Empire in 1897. Data about participation in the census of Tobolsk and the Trans-Baikal committees are provided. The problems of financing, methodological base formation and staffing in the process of census companies are touched upon. The institutions responsible for preparation of the all-Russian population census of 1897 are named. Features of the organization of the first general census in Siberia are investigated. Common features in the development of statistical committees and scientific societies are analyzed separately. The contribution of the Siberian departments of the Imperial Russian Geographical Society, the Society of Altai explorers to the preparation and conduct of population censuses in Irkutsk, Omsk and Barnaul is studied. The author emphasizes the importance of population censuses in the activities of provincial and regional statistical committees, scientific societies of Siberia in the second half of the 19th century.